2011
DOI: 10.1111/j.1532-5415.2011.03488.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Inpatient Geriatric Consultation Team on Functional Outcome, Mortality, Institutionalization, and Readmission Rate in Older Adults with Hip Fracture: A Controlled Trial

Abstract: This trial could not document functional benefits of an IGCT intervention in people with hip fracture. More research is needed to investigate whether a more-intensive approach with more-direct control over patient management, more-specific recommendations, and more-intense education would be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 29 publications
4
106
0
1
Order By: Relevance
“…Other researchers recommend providing discharged patients with a personal health record to help guide outpatient providers (Koehler et al, 2009), giving patients specific instructions about medicines and their health records, following through with home visits, and improving coordination of services and information flow between providers in hospitals and in the community, especially those providers who are in long term services (Deschodt et al, 2011;Dombrowski, Yoos, Neufeld, & Tarshish, 2012;Hansen, Young, Hinami, Leung, & Williams, 2011;Phillips, Wright, Kern, et al, 2004). However, even when a multidisciplinary team approach is employed, lack of communication within the team can lead to poor discharge outcomes (Bauer, Fitzgerald, Haesler, & Manfrin, 2009).…”
Section: Downloaded By [Chulalongkorn University] At 13:02 03 Januarymentioning
confidence: 95%
“…Other researchers recommend providing discharged patients with a personal health record to help guide outpatient providers (Koehler et al, 2009), giving patients specific instructions about medicines and their health records, following through with home visits, and improving coordination of services and information flow between providers in hospitals and in the community, especially those providers who are in long term services (Deschodt et al, 2011;Dombrowski, Yoos, Neufeld, & Tarshish, 2012;Hansen, Young, Hinami, Leung, & Williams, 2011;Phillips, Wright, Kern, et al, 2004). However, even when a multidisciplinary team approach is employed, lack of communication within the team can lead to poor discharge outcomes (Bauer, Fitzgerald, Haesler, & Manfrin, 2009).…”
Section: Downloaded By [Chulalongkorn University] At 13:02 03 Januarymentioning
confidence: 95%
“…12,69,78,80,81,83,87,90-93,95-97,100-103,105-111,114,115,117-124, 130-133,135-140,143,144,146-149,151-158,160-162,167,169,184,192,195,199-201 Sixty-five of these studies reported physical or physiological outcomes, 12,69,78,80,81,83,87,[90][91][92][93]95,97,100,102,103,[105][106][107][108][109][110][111]114,115,[117][118][119][120][121][122][123][124][130][131][132][133][135][136][137][138][139][140]143,144,[146][147][148][149][151][152][153][154][155]…”
Section: Summary Of Outcomesmentioning
confidence: 99%
“…81,97,101,103,112,120,125,128,131,133,135,143,[145][146][147]149,151,152,154,160,161,179,188,195,200,201 Ten of these studies compared some form of community (own home or care home) rehabilitation with hospital-based rehabilitation, 101,103,125,128,131,133,135,143,145,160 with one comparing hospital plus home rehabilitation with hospital rehabilitation only. 133 Eight studies 97,112,120,146,149,151,152,200 compared hospital-based rehabilitation with usual care, no post-discharge care or rehabilitation in nursing facilities.…”
Section: Place Of Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Some studies have shown that CGA incorporated into preoperative assessment may positively predict postoperative outcomes 32-38 with only one exception. 39 Interestingly, it has been proposed a pre-operative algorithm by using geriatric assessment markers. Several markers (i.e., Mini-Cog ≤3, albumin ≤33 g/L, ≥1 fall in past 6 months and haematocrit <35%, dependence ≥1 activity of daily living, comorbidity by using Charlson index M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%